Pengelolaan Pendidikan yang Efektif: Tantangan dan Solusi untuk Masa Depan - Rahmawati, Kesya Aprilia; Dewangga, Puspa Calista; Nurlia, Ririn; Setiawati, Riska; Oktavia, Rizqi; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
Effective education management is key to building quality and sustainable education for the future, especially in the midst of the challenges of globalization and the current digital era. In this study, the main challenges in realizing effective education management such as budget and infrastructure limitations, gaps in access and quality of education, technological developments and digital access are discussed. This study uses literature studies on the challenges and solutions faced to realize effective education management.  Relevant sources related to the topic raised are obtained through Google Scholar. Data analysis uses qualitative descriptive analysis. Based on the results of the study, limited resources and gaps in access to education affect the equitable distribution of education quality and low technological infrastructure hinders creating innovative learning. To overcome the challenges in this study, solutions that can be done are discussed, namely optimizing the education budget, improving infrastructure and equitable access, improving the quality of teachers through teacher training, integrating technology in learning. With collaboration with schools with the government, the private sector, the community and other stakeholders, effective education management for the future can be realized